2017
DOI: 10.1371/journal.pone.0187052
|View full text |Cite
|
Sign up to set email alerts
|

Insight into cordycepin biosynthesis of Cordyceps militaris: Comparison between a liquid surface culture and a submerged culture through transcriptomic analysis

Abstract: Cordyceps militaris produces cordycepin, which is known to be a bioactive compound. Currently, cordycepin hyperproduction of C. militaris was carried out in a liquid surface culture because of its low productivity in a submerged culture, however the reason was not known. In this study, 4.92 g/L of cordycepin was produced at the 15th day of C. militaris NBRC 103752 liquid surface culture, but only 1 mg/L was produced in the submerged culture. RNA-Seq was used to clarify the gene expression profiles of the cordy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
28
0
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 34 publications
(32 citation statements)
references
References 42 publications
3
28
0
1
Order By: Relevance
“…To perform transcriptomic analysis, RNA was extracted from aerial and submerged mycelia following 5, 12 and 19 days of culture. The aerial and submerged mycelia of the 5th day were used to control of the transcriptome analysis, because the mycelia began forming aerial mycelia but did not cover the surface of the medium, and cordycepin production had not yet started (Suparmin et al, ). The results revealed a total of 710 and 1682 DEGs using triplicate samples and a threshold set up of four‐fold change (log2 FC ≥2) and false discovery rate (FDR ≤5%) for the aerial and submerged mycelia, respectively, following 12 days of culture.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…To perform transcriptomic analysis, RNA was extracted from aerial and submerged mycelia following 5, 12 and 19 days of culture. The aerial and submerged mycelia of the 5th day were used to control of the transcriptome analysis, because the mycelia began forming aerial mycelia but did not cover the surface of the medium, and cordycepin production had not yet started (Suparmin et al, ). The results revealed a total of 710 and 1682 DEGs using triplicate samples and a threshold set up of four‐fold change (log2 FC ≥2) and false discovery rate (FDR ≤5%) for the aerial and submerged mycelia, respectively, following 12 days of culture.…”
Section: Resultsmentioning
confidence: 99%
“…The aerial and submerged mycelia of the 5th day were used to control of the transcriptome analysis, because the mycelia began forming aerial mycelia but did not cover the surface of the medium, and cordycepin production had not yet started (Suparmin et al, 2017).…”
Section: Overview Of the Differentially Expressed Genes (Degs) In Tmentioning
confidence: 99%
See 2 more Smart Citations
“…When this fungus inoculated in liquid static culture the submerged mycelia were grown towards the bottom into the medium, and the hypha on the surface of the culture grow into the air and form aerial mycelia after a period of incubation (Figure 1). As we previously reported that cordycepin was produced higher in liquid static than submerged culture [5]. These submerged mycelia that have a direct contact with the medium which might contribute to the secretion of cordycepin.…”
Section: National University Corporationmentioning
confidence: 67%